The Anti-Vaccination Debate: A Cross-Cultural Exploration of Emotions and Epistemic Cognition - Tsuda, Ayano; Muis, Krista Renee (Advances in Social Sciences Research Journal, 2018)
Do vaccines cause autism? Answers to this question have become hotly debated since Web 2.0, where self-authored content continues to grow. If individuals do not have the skills to judge the veracity of information, this can have negative health consequences. Equally troubling is the negative emotions that arise due to the content on vaccination websites, which can be detrimental for learning . We examined source and justification strategies authors used in vaccine websites from USA, Canada, Japan and Chile, and the epistemic strategies and emotions individuals used or expressed while reacting to website content. Analyses revealed that pro-vaccination websites justified claims using quotes from experts. In contrast, anti-vaccination websites relied on sources from personal experience. Results also indicated that anger was prominent in websites that included a balanced or pro-vaccine view, which was consistent across cultures. These results provide insight into the importance of emotions in learning about controversial topics, and shed light into possible cultural differences in formatting arguments. Results may be used to develop interventions designed to change misconceptions about controversial topics that are emotionally driven.